Knowledge mapping and global trends in the field of low-intensity pulsed ultrasound and endocrine and metabolic diseases: a bibliometric and visual analysis from 2012 to 2022 - Chu, Guangdi; Niu, Haitao (Frontiers in Endocrinology, 2023)
Background: Low-intensity pulsed ultrasound (LIPUS) is a highly promising therapeutic method that has been widely used in rehabilitation, orthopedics, dentistry, urology, gynecology, and other multidisciplinary disease diagnoses and treatments. It has attracted extensive attention worldwide. However, there is currently a lack of comprehensive and systematic research on the current status and future development direction of the LIPUS field. Therefore, this study comprehensively analyzed LIPUS-related reports from the past decade using bibliometrics methods, and further conducted research specifically focusing on its application in endocrine and metabolic diseases.We downloaded LIPUS literature from 2012 to 2022 reported in the Web of Science Core Collection Science Citation Index-Expanded and Social Sciences Citation Index, and used bibliometric analysis software such as VOSviewer and CiteSpace to execute the analysis and visualize the results.We searched for 655 English articles published on LIPUS from 2012 to 2022. China had the highest number of published articles and collaborations between China and the United States were the closest in this field. Chongqing Medical University was the institution with the highest output, and ULTRASOUND IN MEDICINE AND BIOLOGY was the journal with the most related publications. In recent years, research on the molecular mechanisms of LIPUS has continued to deepen, and its clinical applications have also continued to expand. The application of LIPUS in major diseases such as oxidative stress, regeneration mechanism, and cancer is considered to be a future research direction, especially in the field of endocrinology and metabolism, where it has broad application value.Global research on LIPUS is expected to continue to increase, and future research will focus on its mechanisms of action and clinical applications. This study comprehensively summarizes the current development status and global trends in the field of LIPUS, and its research progress in the field of endocrine and metabolic diseases, providing valuable reference for future research in this field.